For those who want to see beyond: visual impairment and female empowerment - Farias, Adenize Queiroz de (2020)
In this paper, we present to the eyes of a blind woman who, challenged to review her life story, makes a rereading of remarkable events, from childhood to the present time, involving us in a pleasurable mix between poetry and reality. This is a clipping of the thesis entitled Women's Educational Trajectories: An Intersectional Reading of Disability (Farias, 2017), whose objective is to analyze the effects of empowering and gender structures on the experience of inequalities and multiple vulnerabilities of women with disabilities. Based on the social model, the most recent studies around this issue establish a break with the medical model of disability, now conceived as a condition resulting from experiences of inequalities, as well as barriers that impede the social participation of men and women in this condition. Thus, in reconstructing the life story of a blind woman, we deepen the literature that associates disability with other markers of social inequality, such as gender. The research results show that the biggest challenge to be faced today is to make educational and social structures more accessible, which will offer women, blind and visionaries, mechanisms that allow them to discover their own abilities and thus look at reality. , aware of the force of their transforming action. In this way, we hope to contribute to greater visibility of women with disabilities.